Identification of missense mutations of the KCNJ5 gene on patients suffering from aldosterone-production adenomas in adrenal cortex - Việt, Lê Bắc; Lan, Hoàng Thị; Anh, Lương Thị Lan; Hoàng, Nguyễn Huy (Vietnam Journal of Biotechnology, 2016)
Aldosterone is an important hormone in the adrenal gland as well as the human body. It is responsible for regulating salt and water in the body, therefore controlling blood pressure. Primary aldosteronism (also known as aldosterone producing while suppressing renin) plays a significant role in the pathophysiology of hypertension. Mutation in the KCNJ5 gene which leads to aldosterone-production adenomas is the main cause of primary aldosteronism. In this study, the entire coding sequence of the KCNJ5 gene including 2 exons was amplified and directly sequenced to detect mutations. The result revealed that two missense mutations were identified in two patients with hypertension and an apparent mass on the adrenal gland. A heterozygous mutation, D223V, is a novel mutation while the homozygous mutation, Q282E, was known as a polymorphism that had a significant effect on viability of the H295R cell line and K+ conduction channel. Analysis of the 3D protein structural model of the mutants clarified the relationship between genotype and phenotype of the two patients. These results partially pointed out causes of the adrenal gland adenomas and endocrine disorders in the the patient